An integrated method for net-shape manufacturing components combining 3D additive manufacturing and compressive forming processes - Jiang,J; Hooper,P; Li,N; Luan,Q; Hopper,C; Ganapathy,M; Lin,J (Elsevier, 2017)
Additive manufactured (AM) or 3D printed metallic components suffer poor and inconsistent mechanical properties due to the presence of a large number of micro-voids, residual stress and microstructure inhomogeneity. To overcome these problems, a new forming process has been proposed, which effectively combines AM and compressive forming. The aim of this study is to prove the feasibility of this newly proposed method by providing preliminary results. Thus, we compared the tensile performance of hot-forged additive manufactured stainless steel 316L samples to none-hot-forged additive manufactured ones. Significant improvement in mechanical properties has been found in the tensile tests as well hardness test. In addition, our EBSD characterized grain orientation maps at each stage of the process revealed the corresponding microstructure revolution which provides insights into underlying mechanistic.